A novel aluminum-carbon nanotubes nanocomposite with doubled strength and preserved electrical conductivity - Zhang, Shuai; Chen, Gaoqiang; Qu, Timing; Wei, Jinquan; Yan, Yufan; Liu, Qu; Zhou, Mengran; Zhang, Gong; Zhou, Zhaoxia; Gao, Huan; Yao, Dawei; Zhang, Yuanwang; et al. (Nano research, 2021)
Enhancing the mechanical strength of highly conductive pure metals usually causes significant reduction in their electrical conductivity. For example, introducing phase/matrix interfaces or more grain boundaries, are common and effective methods to strengthen metals. But it simultaneously increases the electron scattering at the interface, thus reducing the electrical conductivity. In this study, we demonstrate that pure aluminum (Al)/carbon nanotubes (CNTs) nanocomposites prepared by friction stir processing have successfully broken through these limitations. The yield strength and tensile strength of Al/CNTs nanocomposites have improved by 104.7% and 51.8% compared to pure Al, while the electrical conductivity remained comparable to that of pure Al. To explore the potential mechanisms, the interface between CNTs and Al was examined and characterized by transmission electron microscopy (TEM) and Raman spectroscopy. Little interfacial reaction compounds were present and no visible physical gaps were observed at CNTs and Al interfaces. We defined it as a clean and tightly bonded interface. Although the quantity of phase interface has increased, the electrical conductivity of the nanocomposite remains approximately unchanged. We attribute the preserved electrical conductivity to the clean and tightly bonded CNTs/Al interface in the nanocomposite.